2016
DOI: 10.1183/13993003.00736-2016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations in primary ciliary dyskinesia: systematic review and meta-analysis

Abstract: Introduction Few original studies have described prevalence and severity of clinical symptoms of primary ciliary dyskinesia (PCD). This systematic review and meta-analysis aimed to identify all published studies on clinical manifestations of PCD patients, and to describe their prevalence and severity stratified by age and sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
190
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 192 publications
(205 citation statements)
references
References 74 publications
7
190
3
5
Order By: Relevance
“…University Hospital Southampton NHS Foundation Trust Pictures shown with consent has an incidence of 1:2,500, approximately four times more common (Lucas et al 2014, Goutaki et al 2016. (Lucas et al 2017).…”
Section: Pcd Carrier Fathermentioning
confidence: 99%
See 1 more Smart Citation
“…University Hospital Southampton NHS Foundation Trust Pictures shown with consent has an incidence of 1:2,500, approximately four times more common (Lucas et al 2014, Goutaki et al 2016. (Lucas et al 2017).…”
Section: Pcd Carrier Fathermentioning
confidence: 99%
“…In PCD, cilia are either static, ineffective or absent, leading to a build-up of mucus in the chest, ears, nose and sinuses. Symptoms occur from the neonatal period onwards and include (Goutaki et al 2016): » Daily chronic wet cough. » Recurrent chest infections leading to bronchiectasis (irreversible lung damage).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review suggested that 58% of women and 100% of men were infertile, but the included studies were highly heterogeneous [1]. MUNRO et al [85] reported azoospermia and oligospermia in a small sample size, with normal motility seen in only one patient.…”
Section: Fertilitymentioning
confidence: 99%
“…Over 20% of patients included in the PCD Registry and 10% of studies included in a recent meta-analysis had diagnosis based on suggestive clinical history only, without diagnostic test confirmation [1,33].…”
Section: Pcd Diagnosismentioning
confidence: 99%
See 1 more Smart Citation